Penerapan Good Corporate Governance dalam Pengungkapan Islamic Social Reporting pada Bank Umum Syariah di Indonesia - Pratiwi, Angrum; Darmawati, Darmawati; Amaliyah, Rizky (El-Barka Journal of Islamic Economics and Business, 2020)
The implementation of Good Corporate Governance (GCG) should be implemented properly, in order to create a healthy banking according to sharia principles. An important part of the governance structure of the Bank is the board of commissioners, directors, and the sharia supervisory board. This study analyzes the effect of GCG disclosure consisting of the board of commissioners, board of directors and sharia supervisory board on Islamic social reporting in Islamic commercial banks in Indonesia. This type of research is associative quantitative. The research sample consisted of seven (7) Islamic commercial banks in Indonesia, with an observation period of 2014-2019. The data source comes from the annual report and GCG report of each Islamic commercial bank. Disclosure of ISR is carried out by means of a dichotomy, namely "1" if the report is disclosed and "0" if not disclosed. Data analysis using multiple linear regression. Hypothesis testing using the t test, F test, and R Square. The results showed that the variable size of the board of commissioners had no effect on the ISR disclosure. Meanwhile, the variable size of the board of directors and sharia supervisory board affects the ISR disclosure. The quality and competence of the board of directors and the sharia supervisory board determine Islamic banks in implementing good corporate governance.Penerapan Good Corporate Governance (GCG) sudah semestinya diterapkan dengan baik, agar terwujudnya perbankan yang sehat sesuai prinsip syariah. Bagian penting dalam struktur tata kelola Bank adalah komisaris, direksi, serta dewan pengawas syariah. Penelitian ini menganalisa pengaruh pengungkapan GCG yang terdiri dari dewan komisaris, dewan direksi dan dewan pengawas syariah terhadap Islamic social reporting pada bank umum syariah di Indonesia. Jenis penelitian adalah kuantitatif asosiatif. Sampel penelitian berjumlah tujuh (7) bank umum syariah di Indonesia, dengan periode pengamatan 2014-2019. Sumber data berasal dari annual report dan laporan GCG masing-masing bank umum syariah. Pengungkapan ISR dilakukan dengan cara dikotomi, yaitu “1” apabila laporan tersebut diungkapkan dan “0” apabila tidak diungkapkan. Analisis data menggunakan regresi linier berganda. Pengujian hipotesis menggunakan uji t, uji  F, dan R Square. Hasil penelitian menunjukkan bahwa variabel ukuran dewan komisaris tidak berpengaruh terhadap pengungkapan ISR. Sedangkan, variabel ukuran dewan direksi dan dewan pengawas syariah berpengaruh terhadap pengungkapan ISR. Kualitas dan kompetensi dewan direksi serta dewan pengawas syariah menentukan bank syariah dalam menerapkan tata kelola perusahaan yang baik.